Respon Dinas Perdagangan Kabupaten Jombang Terhadap Pemberlakuan Pasal 4 Undang -undang Nomor 33 Tahun 2014 Dan Maqashid Syariah tentang Ketentuan Kewajiban Label Halal Makanan Impor - Nely Alfi Rohmah (Journal of Islamic Business Law, 2018)
The study aims to determine the response of the Department of Trade of the Jombang to the implementation of article 4 of Law No. 33 of the year 2014 about Social Security Products Halal and maqashid and portfolio management. This type of research is research the law of the empirical approach juridical sociologica and conceptual approachl. The method of collecting data on primary education obtained through a live interview, data collection has obtained from the literature related. The method of analysis of data used is the method of analysis descriptive. The study concluded that, the Department of Trade of the Jombang to the implementation of article 4 of Law No. 33 of the year 2014 about Social Security Products Halal (Law JPH) to give the affective, because it is still a lot of food products impotts have not labeled as halal and not the sanctions provided by the government to manufacturers of food imports. Furthermore, this is contrary to the concept of maqashid syariah, where the hifz an-nafs in the dharuriyyah can not be used well. Against the easy it is the permintfood imports without a lawful by Departmenen of commerce Jombang